Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Efektivitas Manajemen Pendidikan - Ahmad Irwandi; Mhd. Amrullah; Nurul Aini; Nur Hatikah (Jurnal Manajemen dan Ekonomi Kreatif, 2026)
This study aims to analyze the role of principal leadership in improving the effectiveness of educational management in schools. Effective educational management is highly dependent on the ability of school principals to plan, organize, implement, and evaluate various school programs in order to achieve educational goals. The background of this research is based on the increasing demands for quality education in the era of globalization, which requires strong leadership to ensure that all school resources are managed optimally. This research uses a qualitative approach with a descriptive method to obtain in-depth information regarding the leadership practices of school principals in managing educational activities. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings show that principal leadership plays a crucial role in improving teacher performance, student learning outcomes, and overall school effectiveness. Principals who apply participative, transformational, and instructional leadership styles are more successful in creating a positive school climate and improving educational quality. The study concludes that strong and visionary leadership from school principals significantly contributes to the effectiveness of educational management. Therefore, strengthening leadership competence is essential for improving school quality and achieving educational goals effectively.